Morphobiology And Ranges Of Ants (Hymenoptera: Formicidae) In The Nazarkhan Zone Of The Nizhneamudarya State Biosphere Reserve - Ембергенов М.А; Сабирова З.Ж; Юсупова А.С (Periodica Journal, 2022)
This article presents the distribution of species of the family Formicidae distributed in the Nazarkhan zone of the Nizhneamudarya State Biosphere Reserve. As a result of the conducted scientific experiments, it was studied that the species Cataglyphis aenescens is widely distributed in the Nazarkhan zone of the Lower Amudarya State Biosphere Reserve
Keywords: Research; Lower; Nazarkhan; Formicidae